One-To-One in the Inclusive Classroom: The Perspectives of Paraeducators Who Support Adolescents with Autism Spectrum Disorder - Healy, Christopher (Journal of the American Academy of Special Education Professionals, 2011)
In public schools nationwide, students categorized with Autism Spectrum Disorder (ASD) have traditionally been removed from the general education setting, where they were taught in isolation by special education personnel. More recently, research on the learning needs of students with ASD has suggested the importance of including them alongside their peers. As a result, these students and their paraeducators have entered the classrooms of content area teachers. The context can create challenges for the paraeducator and their special education supervisor who has authority for their training and supervision. This study examined five paraeducators employed in a single high school as they enter general education classrooms to support the particular students they are assigned. Participants discussed the need to understand the full range of behavioral manifestations of autism as a starting point for their work. Once participants acknowledged their student’s differences, however, they identified the instructional context their students needed in order to succeed in the inclusive classroom setting.